2018
DOI: 10.1371/journal.pgen.1007340
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 tumor suppressors in neural crest cells are essential for craniofacial bone development

Abstract: Craniofacial abnormalities, including facial skeletal defects, comprise approximately one-third of all birth defects in humans. Since most bones in the face derive from cranial neural crest cells (CNCCs), which are multipotent stem cells, craniofacial bone disorders are largely attributed to defects in CNCCs. However, it remains unclear how the niche of CNCCs is coordinated by multiple gene regulatory networks essential for craniofacial bone development. Here we report that tumor suppressors breast cancer 1 (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…To reduce off-targeting effects of morpholinos, we co-injected a 1.5-fold (w/w) greater amount of p53 MO together with vwa1 -ATG MO ( Robu et al, 2007 ). Previous research has shown that p53 null mutation in mice can rescue the craniofacial damage caused by disruption of Brca1 ( Robu et al, 2007 ; Kitami et al, 2018 ). We performed injection of p53 at different concentration without vwa1 -ATG MO to rule out its potential effects and no visible malformation was observed at each concentration ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To reduce off-targeting effects of morpholinos, we co-injected a 1.5-fold (w/w) greater amount of p53 MO together with vwa1 -ATG MO ( Robu et al, 2007 ). Previous research has shown that p53 null mutation in mice can rescue the craniofacial damage caused by disruption of Brca1 ( Robu et al, 2007 ; Kitami et al, 2018 ). We performed injection of p53 at different concentration without vwa1 -ATG MO to rule out its potential effects and no visible malformation was observed at each concentration ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…p53 is thought to drive these hematopoietic defects by triggering apoptosis or restraining proliferation, given that Fancd2 −/− mice display increased apoptosis in their HSCs and that lymphoblastoid cell lines generated from Fanconi anemia patients undergo a p53-dependent cell cycle arrest in response to a brief exposure to DNA interstrand crosslinking agents (Ceccaldi et al, 2012). In addition to hematopoietic defects, loss of p53 can also fully or partially rescue other types of developmental defects in animal models of Fanconi Anemia, including the embryonic lethality, craniofacial defects, and pigmentation defects in mice deficient for Xrcc2 , Rad51 , Brca1 , or Palb2 (Table 1), and the growth retardation, microcephaly, and eye defects in Fancd2 -deficient zebrafish (Lim and Hasty, 1996; Xu et al, 2001; Liu et al, 2003; Adam et al, 2007; Bouwman et al, 2011; Tonks et al, 2012; Kitami et al, 2018). Thus, data from various animal models and human patient samples suggest that increased p53 activity, as a consequence of impaired DNA repair, contributes to the hematopoietic defects and other developmental defects in Fanconi Anemia.…”
Section: Increased P53 Activity Contributes To the Developmental Defementioning
confidence: 99%
“…This is evident in the mammalian cranial neural crest where there is an enrichment of DNA repair proteins (Albino et al, 2011). Also, perturbation of the DNA repair protein, BRAC1, induced DNA damage and apoptosis in mice resulting in craniofacial defects (Kitami, Kitami, Kaku, Wang, & Komatsu, 2018). Additionally, Chd1 itself is also known to be critical for DNA repair (Zhou et al, 2018) and the dysregulation of the DNA damage response by CHD1 misexpression is what promotes some forms of cancer (Kari et al, 2018; Mills, 2017).…”
Section: Discussionmentioning
confidence: 99%